Impact of diverse cropping patterns on greenhouse gas emissions: Assessing energy use efficiency in Dinajpur District, Bangladesh - Md. Arifur Rahaman; Alanuzzaman Kurishi, A.S.M.; Cheesman, Stephanie; Hossain, Md. Khaled; Md Nuruzzaman Haque; Huda, Md. Shamsul; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
This on-farm research trials briefly summarize the results of greenhouse gas emissions from a diversified cropping systems after one full cropping cycle. This trial was conducted in the Kalapukur and Indropara villages of the Dinajpur district, addressing total global warming potential, total energy use, and emissions intensity, which are crucial for achieving TAFSSA’s goals. Therefore, the trial aims to emphasize climate change effects to identify strategies to mitigate greenhouse gas emissions from agricultural land.